A review of application, modification, and prospect of melamine foam - Wang Yapeng; Chen Zhaofeng; Lu Yeshang; Yang Lixia; Xu Ting; Wu Haisheng; Zhang Jianxun; He Lihua (Nanotechnology Reviews, 2023)
Melamine foam (MF), a promising development in light materials, finds application in construction, agriculture, aviation, transportation, electronic message, and other fields due to its excellent thermal insulation performance, sound absorption and noise reduction capabilities, safety and health benefits, as well as easy processing. However, its own shortcomings such as hardness, poor toughness, fragility, and slag removal greatly limit its application scope. In this review, a survey of the literature from two aspects of toughening of melamine resin and regulation of MF pore structure are reviewed to explore the research progress of toughening modification of MF. The principle, merit, and demerit of different modification methods are analyzed. In addition, owing to the extensive literature available, this article also summarizes the representative achievements of the nanotechnology modification of MF derivatives (carbon foam and carbon aerogel). Eventually, based on an assessment of current application status for both MF and its derivatives while considering existing challenges in their modification processes using nanotechnology approaches, we discuss future prospects for their application.